Vitamin D Status in Blount Disease. Issue 5 (July 2016) - Lisenda, Laughter; Simmons, Dina; Firth, Gregory B.; Ramguthy, Yammesh; Kebashni, Thandrayen; Robertson, Anthony J. F.
Abstract : Introduction: Blount disease can be defined as idiopathic proximal tibial vara. Several etiologies including the mechanical theory have been described. Obesity is the only causative factor proven to be associated with Blount disease. The aim of this study is to assess if there is an association of vitamin D deficiency and Blount disease. Methods: This a retrospective study of preoperative and postoperative patients with Blount disease who were screened for vitamin D deficiency. Patients with genu varum due to confirmed vitamin D deficiency and rickets were excluded. The study patients had the following blood tests done: calcium, phosphate, alkaline phosphatase, parathyroid, and 25-hydroxyvitamin D (25(OH)D) hormones. Results: We recruited 50 patients. The mean age of these patients was 10.4 years (SD±3.88) with average body mass index of 28.7 kg/m 2 (±10.2). Thirty (60%) patients were diagnosed with infantile, 4 (8%) juvenile, and 16 (32%) adolescent Blount disease. Eight (16%) patients were found to be vitamin D deplete (25(OH)D levels <50 nmol/L). Of these, 8 patients, 6 were insufficient (25(OH)D levels between 30 and 50 nmol/L) and the other 2 were deficient (25(OH)D levels <30 nmol/L). Conclusions: This study showed that the prevalence of vitamin D deficiency in children with Blount disease was similar to that of healthy children living in Johannesburg. There is no evidence that vitamin D deficiency is a factor in causing Blount disease. Level of Evidence: Level III—retrospective study.